Low-Dose Cyclophosphamide Improves Survival in a Murine Treatment Model of Sepsis. Issue 1 (January 2015) - Brown, Ian; Bellevue, Oliver; Shawo, Alexandra; Woldesemayat, Hiwot; Lyo, Victoria; Rayikanti, Benjamin; Lee, Michelle; Uzosike, Ezechinyerem D.; Kasravi, Shiva; Harris, Hobart W.
<x xml:space="preserve">Abstract</x> ABSTRACT Sepsis is a complex medical condition characterized by a systemic inflammatory response in the setting of infection. We hypothesized that combining antibiotics plus an immunosuppressant would protect against the morbidity and mortality of polymicrobial sepsis in mice better than would antibiotics alone. We used a murine cecal-ligation-and-puncture model in which mice were treated either with imipenem plus cyclophosphamide or imipenem alone. Titration to a low cyclophosphamide dose revealed that combination therapy increased survival by 20% compared with imipenem alone (56% vs. 36%, P < 0.001). To investigate the mechanism by which combination therapy did this, we reviewed quantitative and qualitative markers of the systemic immune response, end-organ damage, and the local immune response at the site of injury. Cyclophosphamide treatment was not associated with depletion of peripheral leukocytes or differences in pulmonary damage. However, mice that received combination therapy had higher plasma granulocyte colony-stimulating factor levels than did those treated with antibiotics alone. In addition, mice treated with cyclophosphamide had higher levels of bacterial colonization in intestinal Peyer's patch lymph nodes at 72 h after the septic insult. Intraperitoneal macrophage phenotypes and phagocytosis activity did not differ between groups. We conclude that the inflammatory response plays a significant role in the mortality of polymicrobial sepsis and that the regulation of this element is both feasible and beneficial in this disease model.